FOLKLORE DIGITAL TEACHING MATERIALS CONTAINS MORAL VALUES FROM THE BABAD INDRAMAYU FOR HIGH SCHOOL AND MADRASAH ALIYAH STUDENTS - Suherli Kusmana; Jaja Wilsa; Bela Nurzaman (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to overcome the limitations of folklore teaching materials that highlight the moral values ​​of a region. The development of digital folklore teaching materials containing moral values ​​that are developed based on stories related to the name of a region or area around where students live is very necessary. The use of digital technology can help in developing teaching materials. Utilizing teaching materials from the students' environment will be able to increase students' understanding and is an effort to adapt the materials to students' needs. The method used is research and development using the Analyze Design Development Implement and Evaluate (ADDIE) model. The research process began by analyzing 20 folk tales from the Babad Indramayu which have moral values. From the selected folk tales, folk tales were selected that had moral values ​​that were suitable to be conveyed to high school students. The design of teaching materials balances the results of the analysis of teaching materials containing moral values ​​that are appropriate to the age of the students with the results of the analysis of learning outcomes. The teaching materials that have been developed are validated by experts in teaching materials, literature and learning media. Apart from that, a suitability test was also carried out on teachers as practitioners. After revision of the validation results, an implementation test was carried out in learning. Based on the validation test and suitability test, it is known that the folklore teaching materials developed based on the moral values ​​of the Indramayu community are categorized as very good and suitable for use. Based on the results of trials with Madrasah Aliyah students, it shows that these teaching materials are effective in improving students' moral abilities.